The Magic Key Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
Biff finds an old key in a box, and when it begins to glow, it magically takes her, Chip, and Kipper on an exciting adventure. The key becomes the start of many magical journeys